An Authenticity Analysis of Reading Materials in an EFL Textbook - Syarifah Nur Halima; Kalisa, Pasca (General English Education, 2025)
This research examines the authenticity of reading materials in the English for Nusantara untuk SMP/MTs Kelas IX textbook, using Pinner’s (2014) authenticity continuum theory as the analytical framework. The research employs a descriptive qualitative design through document analysis of five selected reading materials. Seventeen indicators across four dimensions, individual relevance, target language community, classroom applicability, and real-world connection, were used to assess the materials. The findings reveal that the textbooks perform well in terms of structural and pedagogical authenticity, demonstrated by reading materials that are aligned with the curriculum, appropriate to the students' level, and engaging. However, the analysis also revealed a lack of cultural references, real-world content, and opportunities for student interaction, which are crucial for developing communicative competence and cross-cultural awareness. Overall, the textbook offers partially authentic reading materials. It is recommended that future textbook revisions include richer cultural content and more interactive tasks to connect language learning with real-life communication and global contexts.